INTEGRASI ISLAMIC WORLDVIEW PADA PEMBELAJARAN PAUD KURIKULUM MERDEKA: Integrasi Islamic Worldview Pada Pembelajaran PAUD Kurikulum Merdeka - Sari, Anggita; Abas Mansur Tamam; Wido Supraha (Universitas Islam Lamongan, 2024)
The West separates science and religion with the concept of dichotomy, which creates a worrying impact. The goal of Islamic education is to produce qualified and pious humans. This article describes learning integrated with Islamic worldview in the Merdeka Belajar PAUD curriculum, which is a curriculum that has been in effect since 2022. The method used is library research, carried out by collecting and examining data from books or writings that are in accordance with the discussion into primary sources and secondary sources. The results of the study argue that in order to achieve the main goal of Islamic education which is to produce qualified and pious humans, the Learning Outcomes of the Foundation Phase must be integrated with the Islamic worldview, namely by compiling a curriculum that directs students to develop and strengthen the Islamic worldview from an early age